2006
DOI: 10.1002/dvdy.20811
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic and larval expression of zebrafish voltage‐gated sodium channel α‐subunit genes

Abstract: Whereas it is known that voltage-gated calcium channels play important roles during development, potential embryonic roles of voltage-gated sodium channels have received much less attention. Voltagegated sodium channels consist of pore-forming ␣-subunits (Na v 1) and auxiliary ␤-subunits. Here, we report the embryonic and larval expression patterns for all eight members of the gene family (scna) coding for zebrafish Na v 1 proteins. We find that each scna gene displays a distinct expression pattern that is tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 60 publications
4
85
0
Order By: Relevance
“…Recordings from several types of excitable cells also established that RNF121 is required for the transport of functional Na V channels to the membrane of these cells. Taken together with the reported spatial expression of Na V orthologs in zebrafish [RBs, Na V 1.1 and Na V 1.6 (11); skeletal muscle, Na V 1.4; motor neurons, Na V 1.5 and Na V 1.6 (20)], RNF121 is at least required for Na V channel complexes composed of these four α-subunits. However, given its ubiquitous expression in larvae (21), RNF121 might contribute to the quality control of all Na V channels.…”
Section: Discussionmentioning
confidence: 59%
“…Recordings from several types of excitable cells also established that RNF121 is required for the transport of functional Na V channels to the membrane of these cells. Taken together with the reported spatial expression of Na V orthologs in zebrafish [RBs, Na V 1.1 and Na V 1.6 (11); skeletal muscle, Na V 1.4; motor neurons, Na V 1.5 and Na V 1.6 (20)], RNF121 is at least required for Na V channel complexes composed of these four α-subunits. However, given its ubiquitous expression in larvae (21), RNF121 might contribute to the quality control of all Na V channels.…”
Section: Discussionmentioning
confidence: 59%
“…Nav1.1lb belongs to a family of at least eight voltage-gated sodium channels encoded in the vertebrate genome (Novak et al, 2006). Although its mutation causes a rather specific behavioral defect, we found that this channel is expressed rather broadly in the CNS.…”
Section: Discussionmentioning
confidence: 67%
“…This was confirmed by quantitative PCR (data not shown). Similar to other voltage-gated sodium channels (Novak et al, 2006), the gene is broadly expressed in the brain (Fig. 10).…”
Section: Genetic and Functional Identification Of Didy S552 As A Nullmentioning
confidence: 89%
See 1 more Smart Citation
“…The involvement of voltage-gated Na 1 channels in zebrafish embryos and larvae was reported by Novak et al (2006), who showed the embryonic and larval expression patterns for eight members of the gene family (scna) coding for zebrafish Na 1 channels proteins.…”
mentioning
confidence: 93%